Licensing in the pharmaceutical industry: trends and strategies - KODRIČ, META; NOVLJAN, JONA; PREGELJC, DOMEN; REBSELJ, JURE; RIHTARŠIČ, MARTIN; ČASAR, ZDENKO (Anali PAZU HD, 2024)
The future of pharmaceutical companies is closely tied to their ability to innovate, traditionally achieved within the company. Due to declining productivity in recent decades, companies are shifting toward open business models and external collaboration. Partnerships between large and small industry players facilitate the exchange of ideas, knowledge, capital, and technology, accelerating the development of new drugs. Licensing plays a key role in this, including in- and out-licensing as well as licensing of university technologies. In addition to licensing, mergers and acquisitions are also significant, as different forms of collaboration enhance innovation in the pharmaceutical industry, benefiting both companies and patients.